Influence of Damping Ratio and Dynamic Shear Modulus for Different Locations of Peat - Zolkefle, Siti Nurul Aini; Zainorabidin, Adnan; Harun, Syuhada Fatim; Mohamad, Habib Musa (International Journal of Integrated Engineering, 2019)
In recent years, geologist and soil scientist have increasingly sought out organic soil, including peat in tropical regions to study their characteristics and agricultural potential for new development area. However, few studies had been made to analyse the consequences of cyclic loading onto peat. The aim of this study is to determine and analyse the behaviour of dynamic parameters on different locations of peat using cyclic triaxial test. Sample preparations and testing methods on analysing the dynamic parameters are briefly explained. Results on Index Properties test and Cyclic Triaxial test are presented for all peat locations. It has been concluded that the behaviour of damping ratio, D and dynamic shear modulus, G in PNpt, POpt and SBpt are influenced by its morphology characteristics which controls the basic physical and chemical properties of peat. The structural elements that contained in peat samples such as fibres are could also be the major causes pertaining to the Malaysia’s peat dynamic parameters behaviour.